The significance of lipid profile and positive troponin-I in predicting cardiac event - Pullakanam, S. P. Tejaswi; Barla, Krishna; Nekkala, Ramakrishna; Geriki, Sarvari; A. V., Suresh Babu; N., Hanumanth (International Journal of Research in Medical Sciences, 2021)
Background: Diagnosis of acute cardiac event in the early stage of its onset is important in the treatment process. The development of highly sensitive and specific immunoassays for myocardial proteins such as cardiac troponin-I had made it possible. However troponin indicates cardiac events only after its onset or after cardiac tissue necrosis. Traditionally such high risk subjects were identified using lipid profiles. The identification of subjects with high risk of developing cardiac event in the future is more significant as it will provide time to prevent such incidents. Methods: In this retrospective study data of the 250 patients presented to the emergency department with symptoms of cardiac ischemia who underwent both troponin-I and lipid profiles tests were compared with the lipid profiles of 100 normal healthy subjects (controls). The troponin-I was detected quantitatively when a specimen contains troponin-I above the 99th percentile (TnI >0.3 ng/ml). The total cholesterol, high density lipoproteins cholesterol, very low density lipoproteins cholesterol and triacylglycerol levels were also analyzed and low density lipoprotein cholesterol level was calculated using Friedewald’s formula. Results: Patients with chest pain and positive troponin-I test (with confirmed cardiac event) were found to have significantly elevated levels of total cholesterol, triacylglycerols, low density lipoprotein cholesterol level and significantly reduced high density lipoproteins cholesterol levels when compared to the patients who experienced only chest pain with (negative troponin-I) and healthy controls. Conclusions: An acute cardiac event is best diagnosed by highly sensitive and specific positive troponin-I test (by quantitative method). However, traditional lipid profile levels still can be used in screening the populations to identify those subjects with high risk of developing cardiac event, in those centres where troponin-I test facility is unavailable.